Impact of social media on body image ideals and fashion trends among Malaysian youth - Lim, Ming Xian (2024)

(untitled)
In today's digital age, social media has become an inseparable part of the lives of teenagers, significantly influencing their views on body image and fashion trends. This research delves into how much Malaysian teenagers rely on social media platforms to shape their body image ideals and fashion trends, their perspectives on the authenticity and reality of these portrayals, and the impact this has on their self-esteem and self-image. The study, through an extensive literature review, highlights the widespread influence of social media platforms such as TikTok and Instagram, as well as the role of influencers in shaping behaviours and trends among teenagers. The study also addresses the issue of unrealistic beauty standards portrayed on social media and its potential impacts on body dissatisfaction and low self-esteem. By exploring the experiences and perceptions of teenagers, this research aims to offer valuable insights to develop interventions and strategies that can promote healthier body image perceptions and counter the negative impacts of social media use among teenagers in Malaysia. The findings of this study contribute towards an enhanced understanding of the socio-cultural implications of social media on teenagers' well-being and provide actionable insights for parents, teenagers, and social media influencers to navigate the digital landscape more mindfully.